The Key Role of pH Value in the Synthesis of Titanate Nanotubes-Loaded Manganese Oxides as a Superior Catalyst for the Selective Catalytic Reduction of NO with NH3. (25th December 2013) - Chen, Xiongbo; Cen, Chaoping; Tang, Zhixiong; Zeng, Wenhao; Chen, Dingsheng; Fang, Ping; Chen, Zhihang
Abstract : Titanate nanotubes (TNTs) synthesized by hydrothermal method were increasingly used as the catalyst support for the selective catalytic reduction (SCR) of NO with ammonia. This paper reports the critical process of postwashing to prepare satisfactory TNTs for the uses of SCR catalysts. Herein, alkaline TNTs (TNTs-AL), acidic TNTs (TNTs-AC), and neutral TNTs (TNTs-NE) were synthesized by controlling washing pH value. When these TNTs were utilized as the catalyst supports for manganese oxides (Mn/TNTs-AL, Mn/TNTs-AC, and Mn/TNTs-NE), the key role of pH value was found. Titanate nanosheets, titanate nanorods and titanate nanotubes were dominated in Mn/TNTs-AL, Mn/TNTs-AC, and Mn/TNTs-NE, respectively. MnO2 crystal was observed when using TNTs-AC or TNTs-NE as the support. By contrast, Mn3 O4 and NaNO3 were observed when using TNTs-AL as the support. Mn/TNTs-NE showed the best SCR activity, in line with the largest surface area, the best dispersion, and the most active redox property of manganese oxides. Mn/TNTs-AL showed negligible SCR activity, resulting from the minimum surface area, the Mn3 O4 -dominating crystal structure, and the bad dispersion of manganese oxides.